The Fatty Acid Composition and Properties of Oil Extracted from Seeds of Carum roxburghianum Benth. (Radhuni) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Carum roxburghianum Benth. (Radhuni) seeds of three different places of Bangladesh were investigated to determine the fatty acid composition and physico-chemical properties of extracted oil. The seeds were found to contain oil ranging from 15.31 to 20.32%. The percentage compositions of fatty acids were identified and quantified by Gas Liquid Chromatography (GLC). The saturated and unsaturated fatty acids in extracts were 4.95 to 6.27% and 93.73 to 94.89%, respectively. Among six fatty acids identified in this study, oleic acid contributed the highest portion (76.44 to 79.16%), whereas, linoleic (1.38%), linolenic (15.28 - 15.40%), stearic (0.70%), palmitic (4.95 - 5.57%) and ecosenoic acid (0.51 - 15.73%) together contributed the rest. Physico-chemical properties of the oil extracted were also investigated. The specific gravity, refractive index, optical rotation were recorded as 0.903 to 0.918 at 30°C, 1.465 to 1.470 at 30°C and +8.54° to +9.56° at 26°C, respectively. The chemical properties like saponification value (183.52 - 193.45), iodine value (80.99 - 120.90), peroxide value (23.25 - 36.16), acid value (143.84 - 162.99), ester value (48.12 - 62.03), percentage of unsaponifiable matter (3.56 - 6.51%), Reicher-Meissel value (2.00 - 3.12), Polenske value (4.12 - 6.20) and Henher value (85.12 - 95.56) were determined. Overall Radhuni seeds oil can be considered as a good source of oleic acid. Keywords: Carum roxburghianum; Radhuni seed oil; fatty acid composition; oleic acid; Gas Liquid Chromatography. DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8113 Bangladesh J. Sci. Ind. Res. 46(1), 111-116, 2011